2016
DOI: 10.1007/s10853-016-9856-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between molecular structure, crystallization behavior, and mechanical properties of long chain branching polypropylene

Abstract: The crystallization behaviors and mechanical properties of both linear isotactic polypropylene (iPP) and long chain branching polypropylene (LCBPP) were investigated with differential scanning calorimetry, polarized optical microscopy, and wide-angle X-ray diffraction. The results indicated that the long chain branching (LCB) structure could act as nucleating agent accelerating the nucleation but impeding the crystal growth of LCBPP, and eventually increased the crystallization peak temperature and decreased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 46 publications
(54 reference statements)
3
23
0
Order By: Relevance
“…64,65 While co-monomers hinder crystallization into α-phase effectively, they extend mesophase formation toward lower cooling rates. 66,67 As chain structural feature, LCBs affect iPP crystallization, as they enhance the α-phase nucleation process and increase crystallization temperature of iPP by up to 20 K. [68][69][70][71][72] In turn, spherulitic growth rate of LCB PP is less than for linear PP as found by several authors, also confirmed via unpublished data from our laboratories according to a method described elsewhere. 54 The LCB PP α-nucleation effect is active up to the cooling rate of about 1000 KÁs −1 , and like heterogeneous nucleation, it inhibited mesophase formation.…”
supporting
confidence: 63%
“…64,65 While co-monomers hinder crystallization into α-phase effectively, they extend mesophase formation toward lower cooling rates. 66,67 As chain structural feature, LCBs affect iPP crystallization, as they enhance the α-phase nucleation process and increase crystallization temperature of iPP by up to 20 K. [68][69][70][71][72] In turn, spherulitic growth rate of LCB PP is less than for linear PP as found by several authors, also confirmed via unpublished data from our laboratories according to a method described elsewhere. 54 The LCB PP α-nucleation effect is active up to the cooling rate of about 1000 KÁs −1 , and like heterogeneous nucleation, it inhibited mesophase formation.…”
supporting
confidence: 63%
“…The curve of PP1PE1B shows that structural modification improves the crystallization ability of the PP‐phase, which separates from the PE crystallization peak. Zhou et al and Tian et al explain the higher T c of LCB‐PP with the structure of the polymer itself that acts as nucleating agent and Tabatabei et al connects it with residuals from the production process . Furthermore the melting peak of the modified sample PP1PE1B becomes broader; Δ H m increased at the same time slightly.…”
Section: Resultsmentioning
confidence: 99%
“…Long chain branching (LCB) of PP for example can turn out as an innovative concept to give PP post‐consumer waste a second life with improved material properties, especially considering its melt rheology . LCB causes strain hardening and improves the melt strength of the PP.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, polypropylene has been widely used in various applications because of its good mechanical properties, low density, good chemical, and heat resistance . As an important industrial catalyst, the fourth‐generation Ziegler–Natta catalyst has been widely used to produce polypropylene .…”
Section: Introductionmentioning
confidence: 99%